Taking the biscuit: How Safari privacy policies affect online advertising - Simeon Duckworth; Mateusz Myśliwski; Lars Nesheim (Centre for Microdata Methods and Practice (cemmap), 2023)
Many controversies that beset the digital economy turn on the role of advertising and its use of personal data. We examine the trade-off between privacy and ad targeting accuracy from the advertisers' perspective. By exploiting Apple's gradual restriction, and ultimately the abolition of ad tracking in its Safari browser called Intelligent Tracking Prevention (ITP), we analyse how much advertisers are willing to pay for third-party cookies and how tightening privacy policies affect market outcomes. Our empirical strategy treats Apple's policy change as an exogenous shock to the supply of tracking opportunities and uses a series of event study models to estimate its causal impact. Our novel dataset on billions of online ads spans multiple countries, advertisers, and websites, allowing for a thorough heterogeneity analysis. We find that the estimated treatment effects around the ITP introduction dates are small in magnitude, differ across countries and vary by campaign and type of marketplace. This finding contrasts with anecdotal industry evidence that ads in Safari are sold at a significant markdown relative to other browsers. Moreover, our result suggests that the market failed to adjust immediately to a new, more privacy-sensitive equilibrium.
Keywords: 330; Online-Marketing; Datenschutz; Preis; Nachfrage; Kausalanalyse; Welt